Financial Markets and Firm Dynamics - Cooley, Thomas F; Quadrini, Vincenzo (American Economic Review, 2001)
Recent studies have shown that the dynamics of firms (growth, job reallocation, and exit) are negatively correlated with the initial size of the firm and its age. In this paper we analyze whether financial factors, in addition to technological differences, are important in generating these dynamics. We introduce financial-market frictions in a basic model of industry dynamics with persistent shocks and show that the combination of persistent shocks and financial frictions can account for the simultaneous dependence of firm dynamics on size (once we control for age) and on age (once we control for size). (JEL D21, G3, L2)